Subject Case Marking in Urdu Unergative and Unaccusative Compound Verbs - Warsi, MJ; Tahir, Noman (Nepalese Linguistics, 2024)
This paper examines subject case marking with unergative verbs in Urdu compound verb constructions. Urdu has two types of intransitive verbs: unergative and unaccusative. While intransitive verbs typically take a nominative subject, unergative verbs may optionally take an ergative subject, indicating agentivity. Unergative compound verbs take an ergative subject when the light verb (V2) is transitive, but not when it is intransitive. Unaccusative compound verbs, however, always take nominative subjects as they cannot combine with transitive light verbs. Thus, the transitivity of the light verb influences the ergative marking in unergative, but not unaccusative, constructions.